APPLICATION OF SOME SINGLE AND INTEGRATED INDEX EQUATION TO ASSESS HEAVY METAL IN DIFFERENT SOILS IN ERBIL GOVERNORATE - & et al., Aweez (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
The aim of this study was to application of some single and integrated index equation to assess heavy metal in different soil within Erbil governorate. The 15 different locations (Bahare new, Newroz, New Hawler, Hesarok, Azadi1, Zen city, Atconz city, Pank village, Binaslawa, Darato, Qushtapa, Shaways, Kasnazan, Bahirka, Pirzin) were specifically selected to identify the effects of traffic activities on soil properties. Different heavy metal distribution patterns (As, Cd, Cu, Cr and Zn) were determined from distance 5, 25, 50m roadside. Soil pollution was assessed using many indices including: contamination factor (CF), degree of contamination (Cdeg), Ecological Risk Factor and Potential Ecological Risk Index.The results showed that concentrations of As, Cd, Cr, Cu, and Zn in street dust ranged from (4.60, 1.80, 217.83, 62.14 and 215.18) mg.kg-1 which recorded in Qushtapa, Kasnazan, Atconze city, Hasarok5 and Zen city respectively. The contamination factor and degree of contamination of the trace elements As, Cd, Cr, Cu ,and Zn of soil samples was indicating considerable contamination factor for Qushtapa moderate contamination factor for Kasnazan, while Atconze city, Hasarok5, Zen city showed very high contamination factor, while degree of contamination considerable low degree of contamination. According to the ecological risk factor and RI results Qwshtapa was indicate as low potential ecological risk, Kasnazan had moderate potential ecological risk while Hasarok5 and Zen city considerable high potential ecological risk, except Atconze considerable very high ecological risk, on the other hand for RI index shown considerable very high ecological risk recorded in Hasarok 5 soil samples.